Acinetobacter Non-baumannii Species: Occurrence in Infections in Hospitalized Patients, Identification, and Antibiotic Resistance - Eugene Sheck; Andrey Romanov; Valeria Shapovalova; Elvira Shaidullina; Alexey Martinovich; Natali Ivanchik; Anna Mikotina; Elena Skleenova; Vladimir Oloviannikov; Ilya Azizov; Vera Vityazeva; Alyona Lavrinenko; et al. (MDPI AG, 2023)
Background: Acinetobacter species other than A. baumannii are becoming increasingly more important as opportunistic pathogens for humans. The primary aim of this study was to assess the prevalence, species distribution, antimicrobial resistance patterns, and carbapenemase gene content of clinical Acinetobacter non-baumannii (Anb) isolates that were collected as part of a sentinel surveillance program of bacterial infections in hospitalized patients. The secondary aim was to evaluate the performance of MALDI-TOF MS systems for the species-level identification of Anb isolates. Methods: Clinical bacterial isolates were collected from multiple sites across Russia and Kazakhstan in 2016-2022. Species identification was performed by means of MALDI-TOF MS, with the Autobio and Bruker systems used in parallel. The PCR detection of the species-specific blaOXA-51-like gene was used as a means of differentiating A. baumannii from Anb species, and the partial sequencing of the rpoB gene was used as a reference method for Anb species identification. The susceptibility of isolates to antibiotics (amikacin, cefepime, ciprofloxacin, colistin, gentamicin, imipenem, meropenem, sulbactam, tigecycline, tobramycin, and trimethoprim-sulfamethoxazole) was determined using the broth microdilution method. The presence of the most common in Acinetobacter-acquired carbapenemase genes (blaOXA-23-like, blaOXA-24/40-like, blaOXA-58-like, blaNDM, blaIMP, and blaVIM) was assessed using real-time PCR. Results: In total, 234 isolates were identified as belonging to 14 Anb species. These comprised 6.2% of Acinetobacter spp. and 0.7% of all bacterial isolates from the observations. Among the Anb species, the most abundant were A. pittii (42.7%), A. nosocomialis (13.7%), the A. calcoaceticus/oleivorans group (9.0%), A. bereziniae (7.7%), and A. geminorum (6.0%). Notably, two environmental species, A. oleivorans and A. courvalinii, were found for the first time in the clinical samples of patients with urinary tract infections. The prevalence of resistance to different antibiotics in Anb species varied from <4% (meropenem and colistin) to 11.2% (gentamicin). Most isolates were susceptible to all antibiotics; however, sporadic isolates of A. bereziniae, A. johnsonii, A. nosocomialis, A. oleivorans, A. pittii, and A. ursingii were resistant to carbapenems. A. bereziniae was more frequently resistant to sulbactam, aminoglycosides, trimethoprim-sulfamethoxazole, and tigecycline than the other species. Four (1.7%) isolates of A. bereziniae, A. johnsonii, A. pittii were found to carry carbapenemase genes (blaOXA-58-like and blaNDM, either alone or in combination). The overall accuracy rates of the species-level identification of Anb isolates with the Autobio and Bruker systems were 80.8% and 88.5%, with misidentifications occurring in 5 and 3 species, respectively. Conclusions: This study provides important new insights into the methods of identification, occurrence, species distribution, and antibiotic resistance traits of clinical Anb isolates.